Enhanced mode II fracture toughness of secondary bonded joints using tailored sacrificial cracks inside the adhesive. (1st March 2021) - Wagih, A.; Lubineau, G.
Abstract: The mode II fracture toughness of secondary bonded joints can be improved by creating tailored sacrificial cracks inside the adhesive. To this end, we inserted a PTFE film inside the adhesive bondline during the bonding process to create sacrificial cracks inside the adhesive. We demonstrated the efficiency of this technique through ENF tests that characterize mode II fracture toughness of adhesive-bonded CFRP adherends. We ascribed the improvement in toughness to the reduction of the strain concentration at the crack tip, which delayed the crack propagation and thus improved joint initiation fracture toughness, G I I i, and the maximum load capacity, Pmax . Moreover, after crack propagation, sacrificial cracks arrested the crack propagation at the upper interface, grew secondary backward cracks at the lower interface, and created adhesive ligaments. These three damage mechanisms dissipated more energy during propagation, which improved the propagation fracture toughness, G IIc . The improvement rates depend on the sacrificial crack width and the gap between two successive cracks reaching 96%, 98%, and 25% for G I I i, G IIc and Pmax, respectively, for a 2 mm sacrificial crack width and 5 mm gap. Our approach works well for both thin and thick adhesives and is a simple technique to substantially enhance the toughness of secondary bonded joints. Graphical abstract: Image 1